The scarlet letter - Chan, Crystal S; King, Stacy (Manga classics., 2015)
A powerful tale of forbidden love, shame, and revenge comes to life in Manga Classics: The Scarlet Letter. Faithfully adapted by Crystal Chan from the original novel, this new edition features stunning artwork by SunNeko Lee (Manga Classics: Les Miserables) which will give old and new readers alike a fresh insight into the Nathaniel Hawthorne's tragic saga of Puritan America.